Metropolitan Urban Sprawl and Mobility: Core City Estimation of Financial Losses due to Commuting - Lityński, Piotr (Rozwój Regionalny i Polityka Regionalna, 2018)
The subject of the article situates the research in the field of the costs of uncontrolled suburbanisation. The purpose of the article is an attempt to estimate the losses from commuting residents to a workplace in the core city. The calculations were carried out for the Cracow Metropolitan Area, Poland. It was pointed out that social losses from commuting to work are high and exceed PLN 400 million annually. These losses are a consequence of a non-functional road system being a derivative of the chaotic spatial structure caused by urban sprawl.